Consolidation Analysis in Unsaturated Soils with Non-Darcian Flow - Singh A.; Chakraborty M. (My University, 2025)
This article aims to present numerical solutions of the one-dimensional consolidation in partially saturated soils based on non-Darcian flow caused by non-Newtonian liquid. Two partial differential equations corresponding to water and air phases are used to model the transient process of the consolidating layer having a finite thickness and subjected to vertical loading. The flow of the water phase is assumed to be governed by four parameter-dependent velocity-gradient nonlinear model Except for the Darcian relationship, all other assumptions considered in Terzaghi’s classical one-dimensional consolidation theory for saturated clays are considered herein. The diffusion of air through water and the movement of water vapor is not considered in the analysis. The numerical analyses are performed through the Crank-Nicolson implicit scheme. The results are plotted in terms of dimensionless isochrones and consolidation curves (average degree of consolidation with respect to time) corresponding to both water- and air-phases and different drainage boundary conditions. It is well observed from the numerical simulations that the non-Darcian flow delays the process of consolidation. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.